Análise de viabilidade para implantação de cobertura inflável na indústria da construção civil - Costa, Bruno Henrique Rodrigues (2014)
This study had the objective to analyze the viability to apply a system of inflatable coverage during the construction process of a work located in Guarapuava-PR, comparing this cost with the expenses generated by outages to rain days. Thus, was analyzed how many days of significant rainfall that occur annually in the city to point of paralyzing the work, comparing the spending generated by the hand of idle work with the price of implantation the inflatable coverage which was budgeted. Occur about 20 days significant rainfall for criterion used for classification. The cost of the inflatable coverage area of 2,100 m² is R$ 60,900.00 / month. The construction of a unit of 400 homes that make up the enterprise generates an investment of R$6,431.69 for the employer to pay its employees. The company has an expense of R$302,384.00 with the paralysation and replacement services in the enterprise. There is a difference between R$ 428,416.00 using the inflatable coverage and paralyze the work on rainy days, making unfeasible the use of coverages in this work.